PENGARUH RASIO KEUANGAN, TATA KELOLA PERUSAHAAN, KARAKTERISTIK AUDITOR TERHADAP AUDIT REPORT LAG - RENSIA AMARTAVIA; MUHAMMAD ARIEF EFFENDI (E-Jurnal Akuntansi TSM, 2022)
The purpose of this research is to obtain empirical evidence about the effect of firm size, profitability, leverage, auditor reputation, audit tenure, board size, board independence, audit committee size and complexity of corporate as independent variables to audit report lag as dependent variable. The population in this research is manufacturing companies that listed in Indonesia Stock Exchange (BEI) from 2018 to 2020. The sample used for this research consist of 78 listed manufacturing companies. The selection of these sample used the purposive sampling method with total 234 research data and the data analysis method in this research is used multiple regression analysis. The result in this research indicated that audit tenure and board independence had effect to audit report lag. While firm size, profitability, leverage, auditor reputation, board size, audit committee size, dan complexity of corporate had no effect to audit report lag.